Complications, functional and quality of life outcomes following primary and secondary implantation of penile prosthesis at a tertiary referral center. Issue 2 (April 2018) - Ralla, Bernhard; Goranova, Irena; Börnstein, Niels; Friedersdorff, Frank; Maxeiner, Andreas; Magheli, Ahmed; Hinz, Stefan; Neymeyer, Joerg; Miller, Kurt; Busch, Jonas
Abstract The implantation of a penile prosthesis (PP) may be recommended in patients with severe erectile dysfunction (ED) who do not respond to conservative treatments. The aim of this study was to evaluate complications, as well as functional and quality of life outcomes following primary and secondary implantation of PP at a tertiary referral center. In this retrospective study, a total of 51 patients (41 patients with primary (PPP) and 10 with secondary PP (SPP)) were included. Patients and operative characteristics were recorded and complications were analyzed using the Clavien-Dindo classification. To evaluate satisfaction of patients and their partners, as well as PP long-term function, follow-up data were collected by using questionnaires (Erectile Dysfunction Inventory of Treatment Satisfaction (EDITS) and QLQC30). Fifty-one patients with a median age of 61 years (IQR 52–68) received PP implantation (44 AMS 700, 7 Coloplast Titan). Main causes of ED were after radical prostatectomy (27.5%), diabetes (21, 6%), and other unknown reasons (43.1%). Median time of intervention was 94.5 min (IQR 80.8–110.3) with no significant difference between PPP and SPP. Only one patient undergoing PPP surgery had grade 3 complication. Follow-up data from a total of 43 patients (84.3%) with a median follow-up of 26 months (IQR 17–41 mo) was recorded. At the time of follow-up, 88.4% of the PPs were still functional (PPPn  = 34 (94.4%), SPPn  = 4 (57.1%), p  = 0.024). Overall estimated mean PP survival was 63.0 mo ((95% CI) 56.2–70.8 mo) with no significant difference between PPP and SPP. Overall satisfaction (EDITS und QLQC30) was high in both groups with no significant difference. PP implantation shows to be a safe treatment option in the management of severe ED.